A Fingerprint Recognizer Using Interminutiae Binary Constraint Graph. (27th March 2008) - Benhammadi Benhammadi, F. F.; Hentous Hentous, H. H.; Bey Beghdad Bey Beghdad, K. K.
Abstract : The main aim of this paper is to describe an inter-minutiae binary network-based global matching algorithm. It exploits absolute minutiae features represented by a binary constraint graph. A dynamic tolerance area in the neighborhood of the minutiae combined with the search-rearrangement method on the binary constraint graph is used to perform the global matching. Tests on the public fingerprint databases DB1 and DB2 FVC2002 showed that our approach outperforms those based on the forward tracking search only. The most relevant aspect of this algorithm is that it does not require implicit alignment of the two fingerprint images due to the strong dependencies between minutiae described by the constraint graph.